PENGARUH JUMLAH UANG BEREDAR TERHADAP INFLASI DAN SUKU BUNGA, SERTA TERHADAP INVESTASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Karari Budi Prasasti; Edy Juwono Slamet (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
Introduction: Monetary policy is one of the main instruments of macroeconomic policy. The government with monetary policy is able to influence the level of economic growth, employment, and the rate of inflation. The one of main monetary policy is controlling the money supply. Money supply has a widespread impact on other macro variables. This study analyzes the effect of the money supply to variable inflation and interest rates, as well as the effects of inflation and interest rates to investment and economic growth in Indonesia. Methods: This study used analysis of TSLS (Two Stages Least Square). The data used in Times Series. Data for the period 1973 until 2012. Results: From the tests showed that there was a significant effect of money supply to inflation and interest rates. Inflation and interest rates has no effect on investment in Indonesia partially. While there was the simultaneous effect of inflation and interest rates to Investment in Indonesia. The research showed that significantly the investment influence economic growth in Indonesia. Conclusion and suggestion: Research indicates that the variable in the money supply directly or indirectly have an impact on economic growth in a country, thus appropriate monetary policy should be given such a broad impact in an economy.